IMAGINING FOR REAL - Ingold, Tim, 1948- author. ([S.l.])
1 online resource
Keywords: What does imagination do for our perception of the world? Why should reality be broken off from our imagining of it? It was not always thus, and in these essays, Tim Ingold sets out to heal the break between reality and imagination at the heart of modern thought and science. Imagining for Real joins with a lifeworld ever in creation, attending to its formative processes, corresponding with the lives of its human and nonhuman inhabitants. Building on his two previous essay collections, The Perception of the Environment and Being Alive , this book rounds off the extraordinary intellectual project of one of the world's most renowned anthropologists. Offering hope in troubled times, these essays speak to coming generations in a language that surpasses disciplinary divisions. They will be essential reading not only for anthropologists but also for students in fi elds ranging from art, aesthetics, architecture and archaeology to philosophy, psychology, human geography, comparative literature and theology.